Journalism in COVID-19 Web: Assessing the Gains, Pains, and Perils of Nigerian Journalists in Coronavirus Containment - Odii, Chijioke; Ani, Kelechi Johnmary; Ojakorotu, Victor (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The study evaluated the effect of COVID-19 and the containment measures on Nigerian journalists and journalism practice in Nigeria. The study adopted the descriptive survey research design, with a questionnaire and personal interviews as instruments for data collection. A total of 362 copies of the questionnaire were correctly completed and returned by the respondents, and 25 editors and management staff of selected media organizations in Nigeria were interviewed for the study. The study's findings indicated that Nigerian journalists were actively involved in COVID-19 containment efforts in the country and that COVID-19 containment measures negatively affected journalists' performance and journalism practice in Nigeria. It is recommended, among others, that Personal Protective Equipment (PPE) should be provided for a journalist covering the pandemic, and journalists' fundamental human rights should be respected in COVID-19 containment efforts.